Dose adjustment of cisplatin, etoposide, and ifosfamide according to kidney function: a retrospective analysis and implications for medication safety - Grafe, Carolin; Semrau, Sabine; Hein, Alexander; Beckmann, Matthias; Mackensen, Andreas; Dörje, Frank; Fromm, Martin (Naunyn-Schmiedeberg's Archives of Pharmacology, 2018)
Clearance of cisplatin, etoposide, and ifosfamide depends on kidney function and dosages should be adjusted in patients with renal impairment. However, there is still limited data on the adherence of physicians to dosing recommendations for these drugs in cancer patients with renal impairment. Three thousand four hundred forty-eight prescriptions to 369 patients, treated in the Comprehensive Cancer Center of a German university hospital, were retrospectively evaluated. The administered relative doses of cisplatin, etoposide, and ifosfamide were compared with relative doses recommended at the time of prescription according to the patients' creatinine clearance. Cisplatin is contraindicated according to two German summary of product characteristics (SmPC) in patients with a creatinine clearance < 60 mL/min. Nevertheless, 37 cisplatin prescriptions were made for this group of patients (i.e., 2.0% of all cisplatin prescriptions). According to one German SmPC (valid in the year of data analysis), etoposide dosage should be reduced in patients with a creatinine clearance from 15 to 50 mL/min, while it is contraindicated below 15 mL/min. Thirteen etoposide prescriptions were without dose reduction in patients with creatinine clearance from 15 to 50 mL/min (1.5% of all etoposide prescriptions); one patient received etoposide with creatinine clearance below 15 mL/min. In 8.9% of ifosfamide prescriptions, patients did not receive a reduced dose in spite of respective recommendations. Dosages of cisplatin, etoposide, and ifosfamide are not always adjusted as recommended in patients with renal impairment. Consistent international dosing recommendations (e.g., in SmPCs), preferentially included in clinical decision support systems, should be developed to tackle this problem.
EVALuna2:25784

Medication safety in patients treated with new oral antitumor agents: A prospective, randomized investigation on the impact of intensified clinical pharmaceutical/clinical pharmacological care on patient safety, patient knowledge and patient well-being (AMBORA). Supported by the German Cancer Aid within the Comprehensive Cancer Center Erlangen-EMN - Schlichtig, Katja; Lechner, P.; Grafe, Carolin; Ferstl, B.; Fuchs, F.; Hein, Alexander; Meidenbauer, N.; Sell, C.; Semrau, S.; Pavel, Marianne Ellen; Wullich, Bernd; Neurath, Markus; et al. (2018)
EVALuna2:33795